(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: To evaluate the analgesic effect of the spinal block with different doses of Ropivacaine for Crossen surgery for prolapse organ pelvis at the National Hospital of Obstetrics and Gynecology. Subjects and research methods: The patients were diagnosed with prolapse organ pelvis and were indicated for Crossen surgery. Results: Age, height, and weight were not different (p>0.05). The Ropivacaine 13 mg group had a higher level of sensory block at D4 than the Ropivacaine 11 mg group and the Ropivacaine 12 mg group. The difference was statistically significant with p<0.05. Comparing the Ropivacaine 12 mg group and the Ropivacaine 13 mg group, the Ropivacaine 13 mg group had significantly longer postoperative analgesia. The level of pain relief in the Ropivacaine 11 mg group had a statistically significant difference with the 12 mg and 13 mg groups with p<0.05. No patient in all 3 groups had to change to general anesthesia. Conclusion: Study in 90 patients with different doses of ropivacaine in combination with 30 mcg of fentanyl for Crossen surgery for prolapse organ pelvis, it was recommended to use a dose of ropivacaine 12 mg to ensure the quality of anesthesia and minimal adverse effects.